The impact of language functioning among African American adult learners in an adult basic education classroom - Doris Flowers; Vanessa Sheared (Adult Education Research Conference, 1996)
Dialogue taken from a focus group interview with 6 African Americans and one Latina woman were reviewed and analyzed to determine the significance of black dialect on learning. ‘Group think’ emerged as a construct that allowed for communalism and sharing of their polyrhythmic realities. While they had their own thoughts, they associated with one another based on their common understanding of what is was like to be a minority in this society. Language analysis revealed episodes of dysfluent speaking patterns as well as many characteristics of black dialect which did not interfere with communication throughout the dialogue.